The Implementation of the Principle of Justice (al-’adl) in BPJS Health Services at Hospitals from a Legal Perspective - Yandi, Rus; Zuhri, Basrial; Sibawai, Ahmad (The Future of Education Journal, 2026)
The background of this title is that the principle of justice (al-’adl) in Islamic law is a fundamental concept that demands equality, proportionality, and protection of rights. This principle is important to analyze in the context of its implementation in the health social security system regulated by the state, specifically BPJS Kesehatan, particularly in the contract for services at hospitals. This study aims to analyze the implementation of the al-’adl principle in BPJS health services at hospitals from a legal perspective, examining the alignment of operational practices with the framework of positive law (laws and BPJS regulations) as well as Islamic law (fiqh siyasah and maqasid syariah). The research uses a normative juridical method with a legislative, conceptual, and comparative approach to legal norms. The results show that normatively, the laws on the National Social Security System (SJSN) and BPJS Kesehatan have been formulated with the spirit of social justice in line with maqasid syariah, especially in protecting the right to life (hifzh an-nafs) and property (hifzh al-mal), which could be threatened by potential injustices. Issues such as the dual payment system causing service disparities, inconsistent interpretation of standard tariff rules, and an under-optimized mechanism for complaints and enforcement of rights hinder the realization of justice. This research concludes that although the formal legal basis for BPJS Kesehatan has adopted substantive justice values, harmonization and stronger regulation enforcement at the operational level in hospitals are needed to ensure procedural, distributive, and real justice (al-adl al-haqiqi) for all participants.